Enhancing cadmium extraction potential of Brassica napus: Effect of rhizosphere interactions. (15th April 2021) - Li, Longcheng; Zou, Dongsheng; Zeng, Xinyi; Zhang, Liqing; Zhou, Yaoyu; Anastopoulos, Ioannis; Wang, Andong; Zeng, Qingru; Xiao, Zhihua
Abstract: Brassica napus L. (oilseed rape) was grown with daikon and white lupin in a polyvinyl chloride split pot experiment (with no barrier between the compartments or by a nylon mesh barrier (37 μm) to license partial root interaction, or a solid barrier to stop any root interactions) to examine the effect of rhizosphere interaction on the cadmium uptake. The results showed that shoot and root biomasses of oilseed rape were 40.66% and 26.94% less than that of the monocropped treatment (solid barrier) when intercropping with daikon under the rhizosphere complete interaction. However, the intermingling of roots between oilseed rape and white lupin notably enhanced the dry biomass of oilseed rape by 40.23% and decreased with the reduction of root contact. Oilseed rape intercropping with daikon enhanced the shoot Cd concentration of oilseed rape. The shoot Cd concentration (44.8 mg/kg) of oilseed rape when intercropped white lupin under complete rhizosphere interaction were greater than those of other treatments. Additionally, the intermingling of roots played a positive role in the content of citric and malic acids when intercropping with white lupin. In all systems, the BCF values of oilseed rape >5. Therefore, intercropping with white lupin may contribute to higher biomass and increased uptake Cd by oilseed rape. We can toward sustainable positive effects on phytoremediation that based on a better understanding of rhizosphere processes. Graphical abstract: Image 1 Highlights: Daikon and white lupin rhizosphere effects increased the Cd concentration in oilseed rape. Intercropping with white lupin notably increased the biomass of oilseed rape. The increased root interaction can change the OAs contents were significant effect on the Cd bioavailable. White lupin can enhance the effect of Cd phytoremediation of oilseed rape.